Digital Ijtihad in Determining the Direction of Qibla: Analysis of Accuracy and Limitations of Augmented Reality-Based Applications - Hasan, Abdulloh; Hibaurrohman, Imam Labib; Machzumy, Machzumy; Sodri, Hikmah Wahyu (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2025)
Technological developments have given rise to more than 500 qibla direction measurement applications on Google Playstore, but validation of their accuracy in locations with specific geographical challenges, such as the mountainous topography of Baturraden, has been minimal. Moreover, visitors from outside the area often rely solely on the direction of the prayer mat and do not pay attention to the accuracy of the actual qibla direction. This study aims to analyze the accuracy of qibla direction measurements using Android applications with Augmented Reality (AR) camera technology in prayer rooms and mosques in the tourist location of Baturraden as a form of ijtihad to obtain legal certainty regarding the qibla direction. This study is a field study with a qualitative approach. Qibla direction measurements were taken at eight locations using five different applications: NU Online Super Apps, Duff Qibla Finder, Miqat, Kompas Kiblat (AR), and Arah Kiblat (AR). The results show that most applications performed well, with measurement differences between applications ranging from 0⁰ to 1⁰, which is considered accurate according to Thomas Djamaludin's tolerance. However, the key finding of this study was the significant variation in performance and constraints. The Duff Qibla Finder application showed poor performance and did not refer to the correct qibla direction, as well as using a measurement scale of 65°-435°. In addition, the accuracy of the application was greatly influenced by environmental factors at the research location, such as degradation.